GE_GERICHTE P/14975/2020 vom 13. November 2020 - GE Cour de justice (2020)
PROTECTION DE LA PERSONNALITÉ;FRAIS DE LA PROCÉDURE;SOUPÇON;PRÉSOMPTION D'INNOCENCE | CC.28; CPP.422; CPP.426; CPP.310; CPP.392